Transformative practice and its interactional challenges in COVID-19 telephone contact tracing in Flanders - Slembrouck, Stef; Vandenbroucke, Mieke; De Timmerman, Romeo; Bafort, Anne-Sophie; Van de Geuchte, Sofie (Frontiers in Psychology, 2023)
This article focuses on transformative interactional practice in Covid-19 contact tracing telephone calls in Flanders (Belgium). It is based on a large corpus of recorded telephone conversations conducted by Covid-19 contact tracers with index patients in the period mid-2020 to mid-2022. The calls were conducted through government-contracted commercial call centres. For nearly two years and applied country-wide, this was the most prominent strategy in Belgium for breaking transmission chains. Covid-19 telephone contact tracing with infected patients counts as transformative professional work in two ways. First, in addition to the registration of recent contacts in a relevant time window, the work is oriented to awareness-raising about how patients and their co-dwellers can and should adjust their behaviour by attending actively to critical aspects of the pandemic during an individual period of (potential) infection. This is the terrain of advice, interdictions and recommendations about quarantine, isolation, personal hygiene, etc. In addition, the focus on interactional attention indexes patients’ affect and emotions (e.g., anxiety, worry or anger) in a period of health uncertainty and social isolation. The transformative work thus depends on successfully established rapport and empathetic, responsive behaviour. Our analysis of the recorded conversational sequences focuses on the complexities of client-sensitive and responsive transformative sequences and highlights the constraints and affordances which surround the interactional task of ‘instructional awareness raising’ which is central to telephone contact tracing. Specifically, we detail the following dimensions of transformative sequences: (i) how do contact tracers deal with the knowledge status of clients, (ii) their use of upgrading/downgrading formulations, (iii) the use of humour and other mitigating strategies, and (iv) how contact tracers attend to interactional displays of affect and emotion. In a final section, we tie together our observations about the communication of particularised advice in a context of general measures through the twin notions of categorisation/particularisation-work. The findings in this paper are limited to the first step in the chain of contact tracing, i.e., telephone calls with tested and infected citizens.